2020
DOI: 10.1016/j.cej.2019.123404
|View full text |Cite
|
Sign up to set email alerts
|

Microwave pyrolysis of olive pomace for bio-oil and bio-char production

Abstract: Olive pomace is a widely available agro-industrial waste residue in Europe that has the potential to contribute towards a circular, low carbon bio-economy. This study demonstrated, for the first time, the ability to successfully pyrolyse olive pomace with microwaves for the production of bio-char and bio-oil. It was found that the energy requirement needed to pyrolyse up to 80 % of the olive pomace was as low as 3.6 kJ/g and bio-oil yields up to 30 % were produced. Microwave power did not influence the overall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(29 citation statements)
references
References 69 publications
0
28
0
1
Order By: Relevance
“…In a recent study, MW technology was introduced to the pyrolysis process [ 90 ] and found to greatly enhance the loss of mass. When applying less energy (between 0.88 and 1.94 kJ/g), the mass loss increased with MW power, and the highest yields of bio-oil were achieved with the lowest input of 150 W. With higher energies (from 2.27 to 3.27 kJ/g), the maximum bio-oil was obtained at 450 W. Overall, the 150 W power input generated the greatest mass loss and bio-oil yields of the pyrolysis process.…”
Section: Emerging Food Technologies For Increasing the Sustainabilmentioning
confidence: 99%
“…In a recent study, MW technology was introduced to the pyrolysis process [ 90 ] and found to greatly enhance the loss of mass. When applying less energy (between 0.88 and 1.94 kJ/g), the mass loss increased with MW power, and the highest yields of bio-oil were achieved with the lowest input of 150 W. With higher energies (from 2.27 to 3.27 kJ/g), the maximum bio-oil was obtained at 450 W. Overall, the 150 W power input generated the greatest mass loss and bio-oil yields of the pyrolysis process.…”
Section: Emerging Food Technologies For Increasing the Sustainabilmentioning
confidence: 99%
“…Pyrolysis has been the technology of choice, for olive mill solid wastes (OMSWs) in [70] and [27] and for eucalyptus wood fines in [89], to yield bio-oil and biochar, the former thereafter being valorised to a whole range of platform chemicals. Alternately, by subjecting OMSWs to thermal pre-treatment followed by anaerobic digestion, phenol and biomethane can be obtained [124].…”
Section: Municipal and Industrial Solid Waste And Sewage Managementmentioning
confidence: 99%
“…Besides pyrolysis-based systems, the biochar can be obtained from biomass gasification at high temperatures (>700 • C), by means of microwave heating [96], or from a novel technology that integrates pyrolysis with downstream post-catalytic reforming of its volatile products: thermocatalytic reforming (TCR) process [14].…”
Section: Biochar (Bio-oil Syngas) Production From Olive Mill Waste And/or Pruning Residuesmentioning
confidence: 99%